Guideline for Determining the Mean Glandular Dose According to DIN 6868-162 and Threshold Contrast Visibility According to the Quality Assurance Guideline for Digital Mammography Systems - Sommer, A.; Schopphoven, S.; Land, I.; Blaser, D.; Sobczak, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
As part of the physico-technical quality assurance of the German breast cancer screening program, the threshold contrast visibility and the average glandular dose of every digital mammography system have to fulfill the requirements of the “European guidelines for quality assurance in breast cancer screening and diagnosis” (4th Edition). To accomplish uniform measurements in all federal states of Germany, the physical board of the reference centers developed a special guideline in 2009. Due to recent changes in the guidelines and standards, a second version of the guideline was developed by the reference centers. This guideline describes the determination of the average glandular dose as well as the CDMAM image acquisition and the CDMAM image evaluation. The determination of the threshold contrast visibility can be performed visually or automatically. The determination of the average glandular dose is based on DIN 6868 – 162 and the threshold contrast visibility test is based on the German “Quality Assurance Guideline”.Key Points:• Update of the first guideline due recent changes in the national standards• Description of the procedure for determining the average glandular dose according to DIN 6868-162 • Description of the procedure for determining the threshold contrast visibility according to the Quality Assurance Guideline• In addition to the visual evaluation of the threshold contrast visibility, an automatic evaluation method can be usedCitation Format:• Sommer A, Schopphoven S, Land I et al. Guideline for Determining the Mean Glandular Dose According to DIN 6868-162 and Threshold Contrast Visibility According to the Quality Assurance Guideline for Digital Mammography Systems. Fortschr Röntgenstr 2014; 186: 474 – 481
Keywords: digital mammography; average glandular dose; threshold contrast visibility; CDMAM phantom; mammography screening